Electric Coffee Cart Innovation in Denpasar City and Gianyar Regency as a Response to Changing Consumer Behavior - I Putu Andhika Putra; Ni Made Ary Widiastini Widiastini (Bali Membangun Bali: Jurnal Bappeda Litbang, 2026)
Purpose: This study aimed to analyze electric coffee cart innovation in Bali as a micro-enterprise model that integrated mobility, operational efficiency, and social media-based marketing within the context of increasing price sensitivity and shifting consumer behavior. Research methods: The research adopted a qualitative descriptive approach using a comparative case study in Denpasar City and Gianyar Regency. It relied on secondary data derived from media reports, digital content, and a synthesis of domestic mobile coffee studies alongside recent international literature on food trucks, street food consumption, and electric micromobility. Results and discussion: The findings identified six key drivers of purchase decisions, perceived price fairness resulting from lower cost structures, location-based convenience, product quality and menu variety comparable to coffee shops, eco-friendly innovation image, digital exposure through TikTok and Instagram, and operational consistency supported by centralized production systems. Implication: The study contributed by proposing a Stimulus–Organism–Response framework that integrated technological innovation, consumer perception, and competitive dynamics, offering managerial insights and policy implications for MSMEs in tourism-driven public spaces.